Comparative study on In-hospital Improvement of left Ventricular Ejection Fraction after PCI - Rahman, Md Mukhlesur; Siddique, Md Abu; Haque, KMHS Sirajul; Siddiqui, Md Mahmudur Rahman; Ahmed, Md Khurshed; Azam, Md Golam; Rahman, Fazlur (University Heart Journal, 2008)
The purpose of the study was to identify the impact of percutaneous coronary interventions (PCI) on ejection fraction between patients prior MI and without prior MI. This study was carried out at the University Cardiac Centre, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, during the period between January 2006 to July 2006. Patients without history of prior MI experienced significant improvement of echo EF following PCI (62.30 ± 5.52 vs. 46.63 ± 6.43%, p < 0.001). In short term follow up remarkable improvement of LVEF is observed in patients of PCI who do not have prior MI in compared to patients having prior MI. (University Heart Journal 2007; 3 : 60-62)